2023
DOI: 10.1186/s13102-023-00650-2
|View full text |Cite
|
Sign up to set email alerts
|

Home-based cardio-oncology rehabilitation using a telerehabilitation platform in hematological cancer survivors: a feasibility study

Abstract: Purpose Cardiovascular disease is a competing mortality cause in hematological cancer survivors due to toxic oncological treatment, accumulation of risk factors, and decline of cardiorespiratory fitness. Cardio-oncology rehabilitation (CORE) is an emerging treatment model to optimize the prognosis of hematological cancer patients and survivors; however, its accessibility during the COVID-19 pandemic is poor. The study aimed to evaluate the feasibility, safety, and effect of a 12-week home-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…However, our study results failed to confirm the findings of two smaller studies, which reported a difference of 4.0 ml/kg/min in postmenopausal women [ 48 ], or a reduction in male patients ( n = 21) with colorectal cancer of − 1.7 [ 49 ] in comparison to the change in control patients. So far, home-based exercise or telerehabilitation interventions in cancer patients has demonstrated only minor to moderate effects on functional capacity, measured via the 6-min walking distance or oxygen uptake [ 50 , 51 ]. Nevertheless, minor changes in cardiorespiratory performance result in an inverse and clinically relevant change in mortality risk and contribute to improved health [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, our study results failed to confirm the findings of two smaller studies, which reported a difference of 4.0 ml/kg/min in postmenopausal women [ 48 ], or a reduction in male patients ( n = 21) with colorectal cancer of − 1.7 [ 49 ] in comparison to the change in control patients. So far, home-based exercise or telerehabilitation interventions in cancer patients has demonstrated only minor to moderate effects on functional capacity, measured via the 6-min walking distance or oxygen uptake [ 50 , 51 ]. Nevertheless, minor changes in cardiorespiratory performance result in an inverse and clinically relevant change in mortality risk and contribute to improved health [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The findings reveal the presence of obesity, depression and smoking in the patients which can be managed by conducting physical and telehealth exercises for each patient. In article 122 researchers have highlighted the safety and impact of a home-based cardio-oncology rehabilitation (CORE) intervention utilizing a telerehabilitation among individuals who have survived hematological cancer. The approach encompassed three components: a sensor to measure heart rate, an https://doi.org/10.2147/IJGM.S453903…”
Section: Telerehabilitation Of Cardiovascular and Other Diseasesmentioning
confidence: 99%